The BNC of basic education teachers training: considerations on learning styles (Research, Society and Development, 2020)
This paper aims to analyze the use of learning styles in relation to the BNCFP document, encompassing bibliographic studies related to the proposed theme, characterizing it as descriptive and predominantly qualitative. The research arose before the importance of the teacher and his role in the Brazilian educational scenario. The association of learning styles with teacher training, promotes effective communication and more homogeneous learning in the classroom, as the teacher has the capacity to perceive which is the best learning style for each student. With this knowledge, activities that contemplate all forms of learning can be promoted, thus valuing each student in his particularity. It was found that, within the scope of the BNCFP, there is the indirect use of learning styles, although without their deserved prominence in view of the potential that their understanding can represent in the school life of Brazilians. There is a gap in the BNCFP regarding learning styles, and this can be improved with the insertion of models that contemplate the different learning styles. The teaching posture towards the class is of great relevance, but not enough to make an effective contribution to the improvement of Brazilian education indicators. It is necessary for the teacher to be able to understand and be discerning on what is the best approach to teach his students. For this, the continuing education of these professionals is as necessary as preparing the beginning teacher to work in the classroom.